# discrete math

posted by .

Find the solution to the following recurrence:
an=3an−1+7 for n2 with initial conditions a0=7

• discrete math -

An = 3 An-1 + 7
A0 = 7
A1 = 3*7 + 7 = 28
A2 = 3 * 28 + 7 = 91

## Similar Questions

1. ### Discrete Math

Solve the recurrence relation a_n = -6a_n - 1 + 7a_n-2, n ≥ 2, given a₀ = 32, a₁ = -17. This is what I have figured out so far: polynomial: x² + 6x - 7 distinct roots: 1 and -7 I do not understand how to find C₁ …
2. ### Finite Math

Solve the system of linear equations, using the Gauss-Jordan elimination method. (If there is no solution, enter NO SOLUTION. If there are infinitely many solutions involving one parameter, enter the solution using t for the last variable. …
3. ### discrete math

Find the solution to the following lhcc recurrence: an=3nan-1 for n >or equal to with initial conditions a0=4
4. ### discrete math

Find the solution to the following lhcc recurrence: an=3nan−1 for n2 with initial conditions a0=4.
5. ### Discrete Mathematics (computer science)

Find a formula for the nth term of the recurrence K(n) = 13.5K(n – 1) – 2.7 with K(0) = 5.
6. ### precalculus

Find the first five terms of the given recursively defined sequence. an = 3an − 1 + 9 and a1 = 2
7. ### Discrete Math

True or False? Homogeneous linear recurrence equations are linear combinations of power functions. I think the answer is false because although a homogeneous linear recurrence equation is a linear combination, it is composed of constant
8. ### Maths

A sequence {ai}is defined by the recurrence relation an=40−4an−1 with a0=−4. There exists real valued constants r,s and t such that ai=r⋅si+t for all non-negative integers i. Determine r2+s2+t2.
9. ### Chemistry

Balance the following redox (oxidation-reduction) reaction under basic conditions. (Include states-of-matter under the given conditions in your answer. Use the lowest possible whole number coefficients.) CrO42−(aq) + S2O32−(aq) …
10. ### Urgent math

Find the first five terms of the given recursively defined sequence. an = 3an − 1 + 6 and a1 = 1 a1= a2= a3= a4= a5=

More Similar Questions